Incidence trends in prostate cancer among men in the United States from 2000 to 2020 by race and ethnicity, age and tumor stage - Du, Xianglin L.; Gao, Daoqi; Li, Zhuoyun (Frontiers in Oncology, 2023)
Purpose To explore whether prostate cancer incidence trends from 2000 to 2020 in the United States differed by race and ethnicity, age and tumor stage; to explore racial differences in prostate cancer incidence change due to the impact of COVID-19 pandemic lockdown in 2020; and to determine if there is any high-risk population that can be targeted for prevention. Methods We identified 1,098,349 men who were diagnosed with incident prostate cancer at age ≥20 in 2000-2020 in 17 registries of the Surveillance, Epidemiology, and End Results (SEER) program in the United States; of whom, 778,437 were non-Hispanic whites, 155,111 non-Hispanic blacks, 4,200 American Indians and Alaska Natives (AIAN), 55,267 non-Hispanic Asians/Pacific Islanders, and 105,334 Hispanics. Results Age-adjusted incidence rate of prostate cancer was the highest in blacks (302.6 cases per 100,000 men), followed by whites (186.6), Hispanics (153.2), AIAN (108.5), and Asians (104.9). Age-adjusted prostate cancer incidence rates dramatically decreased from 2000 to 2013 for all ethnic men. However, age-adjusted prostate cancer incidence rates increased from 2014 to 2020, in which the increasing incidence trend looked sharper in blacks and whites, flatter in Asians, and leveled in AIAN and Hispanics. Among men with local or regional stages across all years, prostate cancer incidence rate was significantly higher in blacks, but significantly lower in Hispanics, AIAN, and Asians as compared to whites. Among men in 2007-2013, the risk of distant stage prostate cancer was statistically significantly elevated in blacks (rate-ratio: 2.22, 95% CI: 2.06-2.38) and Hispanics (1.16, 1.06-1.25), not significantly different in AIAN (1.30, 0.92-1.76), but still significantly lower in Asians (0.73, 0.66-0.82) as compared to whites. There was a drop of prostate cancer incidence from 2019 to 2020 likely due to the impact of COVID-19 pandemic lockdown on the access to medical care in 2020. Overall prostate cancer incidence rate decreased by 40.4 cases per 100,000 population from 277.4 in 2019 to 237.0 in 2020 for blacks, 20.9 from 164.2 to 143.3 for whites, 16.8 from 124.8 to 108.0 for Hispanics, 14.9 from 101.7 to 86.8 for AIAN, and 12.6 from 88.4 to 75.8 for Asians. Conclusion The decreasing trend of prostate cancer incidence from 2000 to 2013 was statistically significant for all ethnic men. There was an increasing prostate cancer incidence from 2014 to 2020. Age-adjusted incidence rate of prostate cancer was the highest in blacks, followed by whites, Hispanics, AIAN, and Asians, regardless of age groups, tumor stages, and time periods. There will also be a need to monitor and investigate the prostate cancer incidence trend during and after COVID-19 pandemic season.